The Voids of Sepharad. The Memory of the Holocaust in Spain - Baer, Alejandro (Política y Sociedad, 2011)
Spain is a country with no immediate historical connection to the Holocaust. However, in recent years discussions about the Holocaust have gained a more significant presence in Spain´s public life. This irruption of the Holocaust in the spheres of politics, education and culture can be explained as a consequence of political and institutional convergence with Europe as well as of the growing debate over the memory of the crimes of the Franco dictatorship. Using as its basis theories of cosmopolitan and transnationalized memories (Levy y Sznaider 2002, Jeffrey Alexander 2002, Huyssen 2002), this paper approaches the memory, or the memories, of the Holocaust in Spain. The globalized significance of the Holocaust permits different groups to define their own traumatic experiences by creating parallels with the Holocaust, it allows projections and comparisons of different types, and triggers significant resistances and rejections. This essay also argues that the unfortunate historical link to everything related to Jews in Spain, the effects of which are still present, shapes the ways the Holocaust is remembered in contemporary Spain.
Keywords: Holocaust; memory; Genocide; Civil War; Spain; Commemoration; anti-Semitism.